The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10557-008-6089-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nitrate Use in Acute Myocardial Infarction (The Heart Institute of Japan, Department of Cardiology Nitrate Evaluation Program)

Abstract: Our results suggest that nitrate therapy does not increase mortality and cardiac events in AMI patients. Our results differ from those of previous observational studies, suggesting that new prospective randomized clinical trials are needed in the current revascularization era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, the author acknowledged the limitation of the study, as the difference may be attributed to, among other uncontrolled factors, an increased frequency of nitrate use in patients with more severe conditions. 79 Information on the consequence of nitroglycerin tolerance will be valuable for a better clinical use of nitroglycerin and other nitrates in the treatment of patients with angina-related cardiovascular diseases.…”
Section: Angina Nitroglycerin Bioactivation Tolerance and Aldh2mentioning
confidence: 99%
“…However, the author acknowledged the limitation of the study, as the difference may be attributed to, among other uncontrolled factors, an increased frequency of nitrate use in patients with more severe conditions. 79 Information on the consequence of nitroglycerin tolerance will be valuable for a better clinical use of nitroglycerin and other nitrates in the treatment of patients with angina-related cardiovascular diseases.…”
Section: Angina Nitroglycerin Bioactivation Tolerance and Aldh2mentioning
confidence: 99%
“…A meta-analysis of the use of nitroglycerin and nitroprusside (NO donors) in acute myocardial infarct suggested that nitrates reduced mortality be around a third (Yusuf et al, 1988). Conversely, more recent studies failed to identify any benefits or improved clinical outcome associated with long-term nitrite usage (Group, 1994; Yamauchi et al, 2008), whilst another study suggested that nitrate therapy subsequent to acute coronary events increased mortality (Nakamura et al, 1999). However, while the effect on mortality have varied significantly, NO targeted therapeutics appear to be cardioprotective.…”
Section: Nitric Oxide and Caveolin-1 Therapeuticsmentioning
confidence: 99%
“…In this issue of the journal, Yamauchi et al [1] provide further insights into the above observational studies and highlight the importance of patient selection bias. In their study, they initially assessed over 3,000 consecutive Fig.…”
Section: What Is the Clinical Evidence?mentioning
confidence: 99%